Chitosan/polyester-based scaffolds for cartilage tissue engineering: assessment of extracellular matrix formation - Silva, M. L. Alves da (2010)
Naturally derived polymers have been extensively used in scaffold production for cartilage tissue engineering. The present work aims to evaluate and characterize extracellular matrix (ECM) formation in two types of chitosan-based scaffolds, using bovine articular chondrocytes (BACs). The influence of these scaffolds’ porosity, as well as pore size and geometry, on the formation of cartilagineous tissue was studied. The effect of stirred conditions on ECM formation was also assessed. Chitosan-poly(butylene succinate) (CPBS) scaffolds were produced by compression moulding and salt leaching, using a blend of 50% of each material. Different porosities and pore size structures were obtained. BACs were seeded onto CPBS scaffolds using spinner flasks. Constructs were then transferred to the incubator, where half were cultured under stirred conditions, and the other half under static conditions for 4 weeks. Constructs were characterized by scanning electron microscopy, histology procedures, immunolocalization of collagen type I and collagen type II, and dimethylmethylene blue assay for glycosaminoglycan (GAG) quantification. Both materials showed good affinity for cell attachment. Cells colonized the entire scaffolds and were able to produce ECM. Large pores with random geometry improved proteoglycans and collagen type II production. However, that structure has the opposite effect on GAG production. Stirred culture conditions indicate enhancement of GAG production in both types of scaffold.